4(z-2)=2(z+3)

Simple and best practice solution for 4(z-2)=2(z+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(z-2)=2(z+3) equation:


Simplifying
4(z + -2) = 2(z + 3)

Reorder the terms:
4(-2 + z) = 2(z + 3)
(-2 * 4 + z * 4) = 2(z + 3)
(-8 + 4z) = 2(z + 3)

Reorder the terms:
-8 + 4z = 2(3 + z)
-8 + 4z = (3 * 2 + z * 2)
-8 + 4z = (6 + 2z)

Solving
-8 + 4z = 6 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
-8 + 4z + -2z = 6 + 2z + -2z

Combine like terms: 4z + -2z = 2z
-8 + 2z = 6 + 2z + -2z

Combine like terms: 2z + -2z = 0
-8 + 2z = 6 + 0
-8 + 2z = 6

Add '8' to each side of the equation.
-8 + 8 + 2z = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 2z = 6 + 8
2z = 6 + 8

Combine like terms: 6 + 8 = 14
2z = 14

Divide each side by '2'.
z = 7

Simplifying
z = 7

See similar equations:

| 55*t=400 | | 40+1.75c=3.75c | | 82=3(-3x+3)+1 | | -10k+1=40-7k | | 9/20= | | (x+7)x^2-(x+(-2))(x+(-1))=0 | | .07p+4.6=7.3-0.2p | | a=-2x^2+600x | | 1/2-x=1/2 | | -2x^2+6=0x | | 9/22= | | -5c+d+e=-26 | | -7x+3y=30 | | 32x-16= | | (60*4.5%*0.075)/(160-2*0.015)= | | 2x-2=p | | 3y=-2x+24 | | 7x-17=5x+1 | | 8(x+7)=6(-4) | | log(6x+2)=1+log(x-3) | | 2(l+5w)=42 | | 0.12xY=1.2 | | 2580+2920+x=3000.3 | | 4[v-5]=16 | | 36+-4k=-64+-24k | | [c+3]=15 | | -5x-19=-13x | | 45n+7776=75 | | Hg(x)=3.08(120)sqrt+18.97 | | 10x=6.5 | | 57.95=50.45+60 | | 3n^2-10n+5=0 |

Equations solver categories